PS10:184 Constrictive pericarditis as the first presentation of systemic lupus erythematosus: a case report and literature review. (21st March 2018) - Jethwa, H; Rana, M; Kitt, J; Democratis, J; Menzies, S; Steuer, A; Gindea, S
Abstract : Objective: Although fibrinous and exudative pericarditis is a common feature of Systemic lupus erythematosus (SLE), found in 62% of lupus patients on autopsy, very few cases progress to (effusive) – constrictive pericarditis. We describe the unusual occurrence of constrictive pericarditis (CP) in a patient with Systemic Lupus Erythematosus. Methods: This is a chart review- based report of a lupus patient who had constrictive pericarditis as a presenting feature and a systematic literature review of previously published cases. We searched the English medical literature from 1963 to 2016 using PubMed, for terms: 'systemic lupus erythematosus' and 'constrictive pericarditis'. Results: A 49 year old African man presented with several weeks of malaise, weight loss, cough, breathlessness, peripheral oedema and hepatomegaly suggestive of right ventricular failure. An echocardiogram demonstrated features of effusive-constrictive pericarditis. The patient was initially treated for suspected tuberculosis; his symptoms progressed in spite of treatment. Further investigations confirmed positive lupus serology (ANA, anti-dsDNA Ab and anti-Sm Ab, low complement levels) and a raised urine protein: creatinine ratio of 177 mg/mmol. A diagnosis of SLE was established and treatment with Hydroxychloroquine and Prednisolone was initiated. However, the CP was refractory to medical management eventually requiring Pericardiectomy. A literature review identified six other cases of lupus patients with CP. Of these, four patients were male and average age was 38 years. CP was the presenting feature in four cases and TB was part of the differential diagnosis in five cases. The progression from exudative to constrictive pericarditis ranged from one week to six months. Pericardial biopsies performed in four cases showed non-specific chronic inflammation and fibrosis. CP resolved with corticosteroid treatment alone in one case; pericardectomy was necessary in the other five cases for symptom resolution. Conclusions: SLE should be included in differential diagnosis of constrictive pericarditis, especially in 'idiopathic' cases and in the context of poor response to tuberculosis treatment. Pericardial biopsy remains a crucial test in excluding an infectious or malignant aetiology, although the histological findings are typically non-specific for a diagnosis of lupus-related pericarditis. Pericardectomy is likely to be required for definitive treatment.